The Impact of Human Resource Planning on Organisation Performance. A Case of Wamuco Motors Ltd - Stacey Patricia Nakyeyune (Uganda Christian University, 2024)
This research explored the impact of Human Resource Practices (HRP) on organizational performance at Wamuco Motors Ltd., integrating both qualitative and quantitative methods. The study focused on key HR practices, including workforce planning, demand forecasting, skills assessment, succession planning, recruitment strategies, training and development, employee retention strategies, use of technology, and HR metrics and analytics. Data was collected through surveys, interviews, and focus groups with employees and HR professionals, analyzed using thematic analysis, excel and R-studio. The findings revealed that effective HR practices significantly enhance organizational performance metrics such as financial performance, customer satisfaction, employee satisfaction, innovation capacity, operational efficiency, market share, employee productivity, organizational reputation, and quality of products/services. Skills assessment and the use of technology emerged as the strongest predictors of positive performance outcomes, with robust correlations indicating their critical role in driving organizational success. Employee retention strategies also showed strong positive impacts, underscoring the importance of retaining skilled employees. However, the study identified areas for improvement, particularly in succession planning and the application of HR metrics and analytics. Enhancing these practices could further optimize performance and ensure sustainable growth. The research concluded that by investing in and refining HR practices, Wamuco Motors Ltd. can achieve higher efficiency, better employee engagement, and stronger market positioning. This comprehensive analysis provided actionable insights for HR professionals and organizational leaders aiming to leverage HR strategies for enhanced performance and competitive advantage.
Undergraduate research